2019
DOI: 10.24251/hicss.2019.250
|View full text |Cite
|
Sign up to set email alerts
|

Principles of Green Data Mining

Abstract: This paper develops a set of principles for green data mining, related to the key stages of business understanding, data understanding, data preparation, modeling, evaluation, and deployment. The principles are grounded in a review of the Cross Industry Standard Process for Data mining (CRISP-DM) model and relevant literature on data mining methods and Green IT. We describe how data scientists can contribute to designing environmentally friendly data mining processes, for instance, by using green energy, choos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Furthermore, one might include more objectives, e.g. generating proposals that require little energy to process by the AI [14] or taking into account behavioral norms expected by people as common for social robots [3,17]. We hope that in the future human-to-AI coaches will help non-experts to better interact with AI systems.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one might include more objectives, e.g. generating proposals that require little energy to process by the AI [14] or taking into account behavioral norms expected by people as common for social robots [3,17]. We hope that in the future human-to-AI coaches will help non-experts to better interact with AI systems.…”
Section: Discussionmentioning
confidence: 99%
“…All the introduced approaches attempt to enable energy awareness in cloud applications, but the workflow enhancement perspective is missing. Some solutions have been proposed for specific types of applications as by Schneider, Basalla, and Seidel, where guidelines are provided for designing Data Mining tasks [40]. Aligning with current trends in cloud application design, we decide to focus on cloud-native applications.…”
Section: State Of the Artmentioning
confidence: 99%
“…Some proposal aimed to estimate energy efficiency of specific applications in embedded systems [11], but cannot be applied in complex cloud infrastructures. From a design perspective, in [30] more specific guidelines are provided focusing only on data mining. Current research mainly focuses on dynamic resource allocation and scheduling according to energy efficiency optimization [4] [35].…”
Section: State Of the Artmentioning
confidence: 99%
“…Thus, the problem is how to motivate application providers to invest in sustainable applications. Existing studies have demonstrated how sustainability can become a strategic value for both organizations and their customers thanks to a proper awareness of the impact on the environment [30].…”
Section: Feasibility and Open Challengesmentioning
confidence: 99%